Evidence of a recent rapid subsidence in the S-E Cyclades (Greece): an effect of the 1956 Amorgos earthquake? - Evelpidou, N.; Melini, D.; Pirazzoli, P.; Vassilopoulos, A. (Continental Shelf Research, 2012)
An underwater geomorphological survey along the coasts of six Cycladic islands (Sifnos, Antiparos, Paros, Naxos, Iraklia and Keros) revealed widespread evidence of a recent 30–40 cm submergence, part of which may have seismic origin. Comparison with information reported from earthquakes having affected the area suggests that at least part of the recent submergence might be an effect of the 1956 Amorgos earthquake. Modelling of the co-seismic and short-term post-seismic effects of the earthquake revealed that part of the observed subsidence may be explained in some of the islands by a fast post-seismic relaxation of a low-viscosity layer underlying the seismogenic zone. However far-field observations are underestimated by our model, and may be affected by a wider deformation field induced by the largest aftershock of the Amorgos sequence, or by other earthquakes.